A dinâmica geoeconômica da cadeia de energia eólica no Brasil - Zanella, Makerli Galvan (2021)
Wind power is one of the renewable energy sources that presents advantages in energy production, but its use in electrical power production is still only complementary and has been widely disseminated with growth projections even more significant for next few years. This study aims to test Brazil on its actual scenery, verifying if it presents the possibility and has all the needed conditions (technology, budget, regulatory mark) for a large-scale production of energy based on wind power, within Brazilian aerogenerators companies being in a national market competition before working international companies. For that we used “research, historical analysis and first and second data base analysis” within systemic approach, technical visits at wind power stations in loco, industry events and tests applications, a fundamental system to reach the major goal. Documents from different national organizations and international authors have been verified, systemized the data from the tests to understand the productive wind power chain. From the theorical methodology reference the discussions that point Brazil, even if there are all the environmental and geographical conditions available, such as having great wind power potential, it has problems presenting technological solutions and budget difficulties. The improvement on both aspects would promote the industry’s development in the national market and would also bring a bigger international spotlight.